2016
DOI: 10.12945/j.jshd.2016.009.15
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Scoring System to Select Optimally Sized Devices for Percutaneous Patent Foramen Ovale Closure

Abstract: Background Patent foramen ovale (PFO) has been linked to cryptogenic stroke, and closure has been reported to improve clinical outcomes. However, there are no clear guidelines to direct device sizing. This study sought to use patient characteristics and echocardiographic findings to create a prediction score for device sizing. Methods This was a retrospective review of patients undergoing percutaneous PFO closure at our institution between July 2010 and December 2014. Demographic and clinical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
0
3
1
Order By: Relevance
“… 15 Interestingly, Venturini et al described a predictive model for PFO device size selection considering 3 factors, atrial septum aneurism, PFO tunnel >10 mm, and male sex, all of them being predictors of a larger disk size for closure. 12 However, in our study, the proportion of patients with right disks >25 mm was similar between male and female patients. Also, the final optimal result determined by the absence of residual shunting by echocardiography was not influenced by sex.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“… 15 Interestingly, Venturini et al described a predictive model for PFO device size selection considering 3 factors, atrial septum aneurism, PFO tunnel >10 mm, and male sex, all of them being predictors of a larger disk size for closure. 12 However, in our study, the proportion of patients with right disks >25 mm was similar between male and female patients. Also, the final optimal result determined by the absence of residual shunting by echocardiography was not influenced by sex.…”
Section: Discussioncontrasting
confidence: 49%
“…The only retrospective study evaluating sex differences in outcomes following PFO closure showed no differences according to sex, but the follow‐up was limited to 3 months. 11 However, recent studies reported additional sex differences among patients undergoing PFO closure, such as potential differences in device size, 12 delayed PFO closure in female patients, 13 and a higher rate of postprocedural atrial fibrillation (AF) among male patients. 14 …”
mentioning
confidence: 99%
“…Accurate determination of PFO size is important for successful PFO closure. 18 An undersized PFO closure device could result in residual RLS, leading to recurrent thromboembolic events or migraine, 19 or suboptimal anchorage to the surrounding structures, increasing the risk of device embolization. 20 The use of an oversized PFO closure device, conversely, could predispose to atrial wall erosion and aortic injury.…”
Section: Resultsmentioning
confidence: 99%
“…Other patientbased factors such as age, sex, body mass index, as well as anatomical factors such as presence of interatrial septal aneurysm, length of tunnel, and size of shunt play a role in the selection of the device. Therefore, this decision has to be made ultimately by the operator [4,[6][7][8]. There is general agreement that balloon sizing is not recommended for device selection [4].…”
Section: Discussionmentioning
confidence: 99%